Keanekaragaman Jenis Kupu-kupu Familia Nymphalidae dan Pieridae di Kawasan Cirengganis dan Padang Rumput Cikamal Cagar Alam Pananjung Pangandaran - Virda Catur Lestari; Tatang S. Erawan; Melanie Melanie; Hikmat Kasmara; Wawan Hermawan (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACTThe diversity of butterflies’ family of Nymphalidae and Pieridae at Cirengganis area and Cikamal Savannah area of Pananjung Sanctuary of PangandaranThe research reported the diversity o.f butterflies of Nymphalidae and Pieridae Families at Cirengganis area and Cikamal Savannah area which located at Pananjung Sanctuary, Pangandaran. The experiment was conducted using visual encounter survey method. The butterflies were caught using sweeping technique. The butterflies were collected and identified. Abiotic factors such light intensity and temperature were measured during observation. The result showed that 13 species of nymphalidae family were identified whilst only 2 species were identified belongs to the family of Pieridae. Butterfly diversity index at Cirengganis and Cikamal Savannah categorized as moderate with value of 2.285647. Vegetation that interacted with the butterflies were Tectona grandis), Psychotria aurantiaca, and Melastoma malabathricum. Furthermore, light intensity and temperature at Cirengganis were detected at 12473.33 lux and 28.6oC, respectively. While at Cikamal Savannah, the light intensity was measured at 26900 lux and temperature reached 33.6oC.Keywords: Visual encounter survey, Abiotic factor, VegetationABSTRAKPenelitian ini melaporkan mengenai keanekaragaman Jenis Kupu-Kupu Famili Nymphalidae dan Pieridae di kawasan Cirengganis dan Padang Rumput Cikamal Cagar Alam Pananjung Pangandaran. Metode yang digunakan adalah metode Visual Encounter Survey (VES). Penangkapan kupu-kupu dilakukan dengan teknik sweeping. Kupu-kupu yang diperoleh dikoleksi dan diidentifikasi. Faktor abiotik seperti intensitas cahaya dan suhu diukur selama pengamatan. Serta diamati pula vegetasi sekitar lokasi pengamatan yang berinteraksi dengan kupu-kupu. Hasil pengamatan diperoleh total kupu-kupu famili Nymphalidae sebanyak 13 spesies dan kupu-kupu famili Pieridae sebanyak 2 spesies. Nilai indeks keanekaragaman kupu-kupu di kawasan Cirengganis dan Padang Rumput Cikamal tergolong kategori sedang yaitu 2,285647. Hasil vegetasi yang diketahui berinteraksi dengan kupu-kupu yaitu jati (Tectona grandis), ki kores (Psychotria aurantiaca), dan harendong (Melastoma malabathricum). Sementara rata-rata intensitas cahaya dan suhu di Cirengganis sebesar 12473,33 lux dan 28,6oC dan di Padang Rumput Cikamal sebesar 26900 lux dan 33,6oC.Kata Kunci: Visual Encounter Survey, Faktor abiotik, Vegetasi